Two-Part Transition or Two-Part Subordinate Theme? - Wiens, Carl (Intersections, 2010)
In William Caplin’s Classical Form (1998), the ending of a sonata-form exposition’s two-part transition and a two-part subordinate theme’s internal cadence share the same harmonic goal: the new key’s dominant. In this article, the author contends that the choice between the two is not as clear-cut as Caplin suggests, arguing that the functional role of these passages should be read within the context of the entire sonata movement, rather than on more localized analytical interpretations of the sonata’s sections taken in isolation. Two works are discussed: the first movement of Beethoven’s Piano Sonata op. 2, no. 3, and the first movement of the Piano Sonata op. 10, no. 2.